Standerdizing time and methods of propagation in mango (Mangifera indica) for vindhya region of Madhya Pradesh (Current Horticulture, 2024)
An experiment was conducted to find out suitable time of grafting and method of grafting in mango (Mangifera indica L.) at J N Krishi Vishwa Vidyalaya, Rewa, during 2010. Various dates of grafting and methods of grafting differed significantly, whereas interaction between date of grafting and method of grafting was significant for all characters. The maximum bud sprouting (83.33%), grafts or bud survival percentage (83.27%), grafts or bud success percentage (73.33%) and saleable plants percentage (73.33%) were recorded in 15 July among all dates of grafting. Whereas minimum bud sprouting (51.65%), grafts or bud survival percentage (52.21%), grafts or bud success percentage (48.88%) and saleable plants percentage (48.88%) were found in 30 December. Thus, it was concluded that date of grafting (15 July) was most suitable for propagation of mango, followed by 30 July and 15 August. Among methods of propagation, patch budding was found superior grafting method. Vindhya region in Madhya Pradesh showed maximum success with production quality of planting material. Mango was prepared by patch budding with maximum survival (86.67%) compared with of other methods.
Keywords: Propagation methods; Vindhya region; Grafting; Bud sprouting; Grafts; Propagation